1982
DOI: 10.1210/endo-111-1-347
|View full text |Cite
|
Sign up to set email alerts
|

DOPAMINE INHIBITS32PiINCORPORATION INTO PHOSPHATIDYLINOSITOL IN THE ANTERIOR PITUITARY GLAND OF THE RAT

Abstract: The in vitro effect of dopamine, haloperidol and pimozide on 32Pi incorporation into phosphatidylinositol, phosphatidylcholine and phosphatidylethanolamine by anterior pituitary glands was studied. Dopamine decreased the incorporation of 32Pi into phosphatidylinositol in a dose-related manner without affecting phosphatidylcholine and phosphatidylethanolamine. Haloperidol and pimozide did not modify 32Pi incorporation into these phospholipids by themselves but completely reversed the inhibitory effect of dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Dopamine interacts with the phosphatidylinositol/Ca2+ mobilization pathway in lactotrophs (Canonico, Valdenegro & Macleod, 1982;Enjalbert et al 1986) and consequently may modulate protein kinase C activity. Since in some cases, the activity of voltage-gated Ca2+ channels and nicotinic ion channels appears to be regulated by protein kinase C-mediated phosphorylation (Levitan, 1985), it is tempting to speculate that the mechanism of action of dopaminergic modulation of adrenomedullary catecholamine secretion might also involve protein kinase C. Apomorphine inhibition was unaltered by PTX pre-treatment, although it is possible in chromaffin cells that PTX-insensitive pathways of phosphatidylinositol hydrolysis exist, as described in other systems (Ashkenazi, Peralta, Winslow, Ramachandran & Capon, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine interacts with the phosphatidylinositol/Ca2+ mobilization pathway in lactotrophs (Canonico, Valdenegro & Macleod, 1982;Enjalbert et al 1986) and consequently may modulate protein kinase C activity. Since in some cases, the activity of voltage-gated Ca2+ channels and nicotinic ion channels appears to be regulated by protein kinase C-mediated phosphorylation (Levitan, 1985), it is tempting to speculate that the mechanism of action of dopaminergic modulation of adrenomedullary catecholamine secretion might also involve protein kinase C. Apomorphine inhibition was unaltered by PTX pre-treatment, although it is possible in chromaffin cells that PTX-insensitive pathways of phosphatidylinositol hydrolysis exist, as described in other systems (Ashkenazi, Peralta, Winslow, Ramachandran & Capon, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of prolactin release from the pituitary gland, the role of intracellular cyclic AMP has not been elucidated. Canonico et al (1982) showed that stimulation of the D2-dopamine receptor inhibits 32p incorporation into phosphatidylinositol in the rat anterior pituitary gland. They suggested that a decrease in phosphatidylinositol cleavage and turnover may be involved in the inhibitory regulation of prolactin release by dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in phosphoinositide hydrolysis due to the stimu lation of a specific phospholipase C cause an increase in diacylglycerol, InsP, and phosphatidic acid -an increase that initiates a cascade of reactions culminating in Ca2 + mobilization and a biological cellular response [9,10]. Our laboratory has investi gated whether several factors that affect PRL release from the anterior pituitary gland have related effects on phosphoinosi tide metabolism.We reported that incorporation of [32P]orthophosphate into the total pituitary gland 'phosphatidylinositol fraction' was greater in tissue obtained from female rats, which had higher levels of serum estradiol, than from male rats [11,12]. Bonnetti et at.…”
Section: Discussionmentioning
confidence: 94%
“…Changes in phospholipid metabolism, in certain specific instances, repre sent an important intracellular event and function as a second messenger from activated receptor sites to processes that direct ly facilitate the release of hormones [10], Earlier reports from our laboratory showed that the incorporation of [32P]orthophosphate into pituitary gland phosphoinositides is greater in tissue obtained from female than from male rats, which raises the possibiliy that estradiol levels may play a role [11,12], It was also reported that marked changes in the incorporation of [32P]orthophosphate into pituitary gland phosphoinositide lipids occur following the injection of a-methyl-a-tyrosine, an inhib itor of dopamine synthesis and enhancer of PRL release. Con…”
mentioning
confidence: 99%